(untitled) (Eurasian Journal of History, Geography and Economics, 2026)
This study examines population growth in Turkestan and the key factors influencing it. It analyzes demographic trends, including birth rates, death rates, and migration processes, while also considering the impact of economic development, social conditions, healthcare improvements, and environmental factors. The research highlights how historical and modern influences have shaped population dynamics in the region. Furthermore, it explores challenges related to rapid population growth and suggests possible strategies for sustainable development.